Analysis of the Implementation of the Basic Immunization Program for Infants during the Covid-19 Pandemic in the Work Area of the Bukittinggi City Health Office - Intan Julianingsih; Roza Sri Yanti; Bobby Indra Utama (Science Midwifery, 2022)
The basic immunization program is a national program from the Government in the field of immunization which is useful for achieving an international commitment, namely Universal Child Immunization (UCI) in infancy. The achievement of the basic immunization program for infants in Bukittinggi City in 2020 is 56.4%, which is still below the national target. The aim of the study was to analyze the implementation of the basic immunization program for infants during the Covid-19 pandemic in the Work Area of the Bukittinggi City Health Office. The research was conducted using a qualitative approach, a case study research design. The research was conducted in the Work Area of the Bukittinggi City Health Office. Selection of research informants with purposive sampling . The results of data processing and analysis on the input component, human resources are sufficient but have dual duties at the Puskesmas. Funds have been budgeted through the BOK budget. Adequate facilities and infrastructure. The number of guidelines/SOPs is still insufficient. Policies from the government affect community activities. Process : the planning and organizing has been done. Implementation of basic immunization is carried out according to the zone of each region/RT/RW. Recording and reporting has been going quite well. Monev during the Covid-19 pandemic was still not optimal, it could not be done routinely. The conclusion of this study is that the input and process components have not been implemented optimally. The achievements of the basic immunization program at the Bukittinggi City Health Center in 2021 are still below the achievement target.